Islamic Republic of Iran - Health Sector Review : Volume 1. Main Report - World Bank (Washington, DC, 2012)
The Government of the Islamic Republic of Iran has stated its commitment to improving the health and nutritional status of the population as articulated in the Interim Country Assistance Strategy (CAS), which lists as priorities addressing nutritional deficiencies, expanding coverage of basic health services, and improving efficiency of the health system and the quality of service at all levels. This health sector review is consistent with this in that it provides the platform and evidence base for such reform. It is also in-line with part three of the current Fourth Five-Year Plan, which includes health development, human security and social justice priority, the reduction of illness from malnutrition, increasing public health service coverage, and increasing access to quality health services while reducing the financial burden on the families. The objective of this study is to provide a comprehensive review and diagnostic of the performance of the health sector in the Islamic Republic of Iran. The government is quite advanced in the type of analysis it already undertakes on various aspects of the sector (e.g., burden of diseases, national health accounts, and utilization analysis). However, a consolidation of this information and analysis that encompasses several major elements of the health sector has not been done recently. The health sector review, through a synthesis of available data and other information on the health sector attempts to: (i) assess the strengths, challenges, and opportunities facing the current health system; (ii) offer analytic assessments of the health policies and plans; and (iii) provide a framework for developing strategic options as well as short- and medium-term recommendations and action plans to achieve the goals identified in the country's Fourth Five-Year Plan. The review is also intended to provide a platform for discussions on possible areas of collaboration between the Government of the Islamic Republic of Iran and the World Bank on the health sector.